RISK FACTORS OF BIRTH TRAUMA TO THE FETUS DURING VAGINAL & CS DELIVERY - Rehab Ajeel Najeeb; Yusra Abbood Mahdi; Alaa Khudhiar Alzaidi (Scholar Express Journals, 2021)
One hundred patients were collected from Al-Rifai Hospital and Habbobi Teaching Hospital for Obstetrics & Gynecology, Thi-Qar, Iraq, and Ibn Al Baladi Hospital for Children and Women, Baghdad, Iraq. With vaginal and cesarean deliveries, and the risks to newborns were measured. Labor, course of delivery-variants of the mother (cesarean section or vaginal), and through the statistical analysis program, the age of the patients was identified 32±4.2, which indicates the actual value and standard regression, and several conclusions were found, including few injuries after birth. Immediately or no symptoms appear after a short time. The child can be diagnosed with torticollis, head asymmetry, a congenital anomaly in the early stages. People with cerebral palsy (CP) result from the most severe congenital injuries, and most damage does not appear immediately after the baby is born and only appears over time. Moreover, birth injury sometimes requires a sufficiently long period to reveal itself. Time bombs include neuropsychiatric disorders (central nervous system (CNS) and peripheral nervous system disorders) -developmental delays, various conditions of the autism spectrum, convulsive syndromes
Keywords: Trauma; CS delivery; vaginal delivery; Newborns